(untitled) (The International Journal for Scientific Research, 2025)
The study aimed to identify the differences between students of the Faculty of Sharia and Law and students of the Faculty of Education at Al-Asmariya University in the city in life satisfaction, optimism and pessimism according to the variable of specialization and the variable of the college (Faculty of Arts - Faculty of Sharia and Law), the researcher used the descriptive approach to suit the purposes of the study, the study sample consisted of 494 male and female students distributed between the Faculty of Sharia and Law and the Faculty of Arts at Al-Asmariya University in the city of Zliten, to achieve the objectives of the study, the researcher used the life satisfaction scale of Amani Abdel Maqsoud after some modifications were made to it, and the Arab list of optimism and pessimism by Ahmed Abdel Khaleq, the researcher also used the following statistical methods: arithmetic mean, standard deviation, variance, skewness, correlation coefficient, (T) test to determine the significance of the differences between the average scores of the sample members, and the equation (Cohen’s d), one-way analysis of variance, and Tukey’s test for multiple comparisons, the study concluded: There are statistically significant differences between the students of the sample in life satisfaction according to the variable of specialization in the dimensions the following: self-satisfaction, family satisfaction, social satisfaction, and satisfaction with study, there are no differences in life satisfaction among the sample students in the dimension of being free from neurotic symptoms, there are statistically significant differences among the sample students in optimism and pessimism according to the specialization variable, there are statistically significant differences among the sample students in life satisfaction according to the college variable (Faculty of Sharia and Law - and Faculty of Arts), the differences were in favor of the Faculty of Sharia in the dimension of family satisfaction and social satisfaction, There are no statistically significant differences among the sample students in optimism and pessimism according to the college variable (Faculty of Sharia and Law - and Faculty of Arts).